Role of female community health volunteers for visceral leishmaniasisdetection and vector surveillance in Nepal - Mazin Omer; Axel Kroeger; Anand Ballabh Joshi; Murari Lal Das; Lina Ghassan Younis; Vivek Kumar Singh; Chitra Kumar Gurung; Megha Raj Banjara (Tabriz University of Medical Sciences, 2020)
Background: As visceral leishmaniasis (VL) has recently expanded in previously non-endemic areas of Nepal, the health system is facing new challenges. Female community health volunteers(FCHVs) are playing an important role for VL elimination in Nepal. This study aimed to analyze the actual and potential role of FCHVs for VL elimination program as well as community awareness of the disease (VL) and protective measures. Methods: We used a concurrent embedded mixed methods design. Qualitative data were collected through in-depth interviews and focus group discussions with FCHVs of 22 VLendemic villages of 3 districts. Concurrently quantitative data were collected through formal interviews of 203 household heads of the same villages. Results: FCHVs are able to perform their duties in an efficient way with the support of their families and specific incentives. FCHVs in the VL-endemic region have a good ability to recognize the VL suspects and refer to health facilities. The feedback by the district health office on referred patients was weak thus missing the opportunity of involving FCHVs in the 6-months follow up. In houses with a previous VL case knowledge levels of prevention and treatment ofVL were significantly better than in houses without a previous VL case. More people in houses with a former VL patient were aware on VL transmission. Conclusion: FCHVs are playing an important role for VL elimination in Nepal through detection of suspected cases and referral and may play a role in vector surveillance.